KEBEBASAN DALAM EKONOMI ISLAM - Kartini; Wahab, Abdul; Ayu Oktoviasari, Vera (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Islam has economic principles, one of which is the principle of freedom. Freedom in liberal and Islamic economic systems is interesting to study. This research aims to explore the meaning of freedom in the principles of freedom in Islamic economics and how it differs from freedom in the context of liberal economics. This research is library research using a qualitative paradigm. The data comes from various literature such as books, scientific journals and relevant articles. The result of the study in this paper is that freedom in the Islamic view is the freedom for every human being to take all actions necessary to obtain the highest benefit. In its implementation, the principle of freedom can be practiced in various ways, both individually and in groups, in thought and action, and theologically or ushul fiqh.